Tekne and phronesis (Devenires, 2001)
This essay comes back to the classical relationship problem between theory and praxis through a development of an opposition inside the “technical knowledge” concept (tekne) and the “practical knowledge” concept (phronesis). It is produced a critic to the technical activity model - the model used by modern thought in most of its varieties to think the relation between theory and praxis. We agree to come back to the Aristotelian concept of “phronesis”, by widening and “tingeing” its meaning and implicative spectrum. The statement mainly arises from the hermeneutical thought of Heidegger and Gadamer, eventhough we also include a group of references of thinkers close to hermeneutics, as Hannah Arendt, Maurice Merleau-Ponty, Jürgen Habermas, Alasdair MacIntyre, Charles Taylor. Anthropological ideas from Tzvetan Todorov and Michael Carrithers are strongly considered as well. Classical thinkers like Aristotle, Kant, Schiller and Marx are refered too.
Keywords: tekne; phronesis